Measurements of the neutron total cross-sections of tantalum by using pulsed neutrons based on an electron linac - Meaze, A.K.M.M.H.; Lee, Y.Y.; Yoo, K.J.; Kim, Y.A.; Namkung, W.; Ko, I.S.; Cho, A.H.; Kang, H.; Lee, Y.S.; Son, D.; Kim, G.; Khandaker, Mayeen Uddin; et al. (2006)
The neutron total cross-sections of tantalum (Ta-181) were measured in the neutron energy region from 0.01 eV to 100 eV by using the time-of-flight method at the Pohang Neutron Facility, which consists of an electron linac, a water-cooled tantalum target with a water moderator, and a 12-m-long time-of-flight path. A Li-6-ZnS(Ag) scintillator with a diameter of 12.5 cm and a thickness of 1.6 cm was used as a neutron detector, and a natural tantalum metal plate, 10 x 10 cm 2 in area by 0.45 mm in thickness, was used for the neutron transmission measurement. The background level was determined by using a notch-filter of Co, In, and Cd sheets. The present measurement was compared with the previous ones and the evaluated data in ENDF/B-VI.8. The resonance parameters of Ta-181 isotope were obtained from the transmission ratio by using the SAMMY code, which utilizes both Doppler and resolution broadening effects and Bayes' generalized least squares technique.